PEMBUATAN MESIN PRESS HIDROLIK MANUAL BERKAPASITAS 20 TON - -, Hartono (Nozzle : Journal Mechanical Engineering, 2023)
Abstract  A manual hydraulic press machine with a capacity of 20 tons is a production tool that functions to press or press thick-layered workpieces with the help of a hydraulic pump. The aim of this research is to determine the process of making a manual hydraulic press machine with a capacity of 20 tons. In this research, the research method used is a descriptive qualitative research method, because this research will only explain the process of making a 20 ton capacity manual hydraulic press machine, therefore research activities are only limited to finding out about tools and materials. what is needed in the process of making the machine and also about the process of making the machine. Based on research, the appropriate materials used in the process of making a 20 ton capacity manual hydraulic press machine are materials that have been well tested, such as UNP ST 37 iron material which produces a maximum tensile strength of 481,559 N/nm2 with a loading force of 77, 5000 kN. and in testing assental iron with a diameter of 16mm and a length of 24cm, it produces a bending test of 17.6044 kgf/mm2 with a loading force of 3,575.06 kgf, has a yield load of 56.4063 kN and a tensile load of 350.490 N/nm2. Apart from that, in making a manual hydraulic press machine with a capacity of 20 tons, there are several processes, namely design, measuring, cutting, welding, smoothing, assembling, punching, and painting and tensile testing on ST 37 steel plates.